LAPORAN KASUS: REAKSI KUSTA YANG DIDUGA DICETUSKAN OLEH INFEKSI COVID 19 - Laras Maranatha Tobing; Antoni Miftah; Desidera Husadani; Natalia Wahyudi (Media Dermato-Venereologica Indonesiana, 2023)
Background: Leprosy is one of the oldest and most neglected diseases in the world. During the COVID-19 pandemic, leprosy reaction triggered by COVID-19 has not been widely reported. Case: A 38-year-old woman, complained of erythema nodules in the eyelids for 1 week, increasing in size and pain accompanied by fever and nasal congestion. There is no previous history of disease or treatment. Physical examination revealed increased body temperature and anemia with bilateral madarosis. Dermatological status showed multiple erythematous nodules with regional distribution on bilateral superior palpebrae that were palpable with pain. There were multiple lesions of erosion and excoriation in the bilateral plantar pedis region. Sensory function is impaired with stocking hypoesthesia of the digits and lateral plantar pedis bilaterally. The results of the laboratory examination were SARS-CoV-2 PCR positive, ELISA anti PGL-1 IgM 8,159 u/ml, IgG 1,421 u/ml and the Bacterial Index (IB) 3+. Histopathology HE demonstrating lobular panniculitis with vasculitis and FF negative AFB. Discussion: Based on the medical history, physical examination and laboratory, the patient was diagnosed with an Erythema Nodosum Leprosum (ENL) reaction in a new case of Morbus Hansen (MH), suspected to be triggered by a COVID-19 infection. Neutrophil activity and cytokine storms due to COVID-19 are thought to trigger the ENL reaction. Conclusion: In the pandemic era, COVID-19 infection needs to be watched out for as a possible trigger for leprosy reaction.